Gastro-Duodenal Protective Effect of Functional Food Powder Made from Medicinal Plants Grown in the Northwest - Tung, Bui Thanh; Thu, Dang Kim; Thanh Hai, Nguyen; Thanh Hang, Luc Thi; Trang, Nguyen Thi; Thi Thanh Duyen, Bui; Dinh Hoa, Hoang; Thi Minh Ly, Nguyen (VNU Journal of Science: Medical and Pharmaceutical Sciences, 2018)
Abstract: Gastric-duodenal ulcer is one of the most common digestive disorders. Medicinal plants are often used in traditional medicine to prevent and treat symptoms such as inflammation, gastritis and gastric-duodenal ulcer. This study evaluates the protective effect of the prepared functional food from Oryza sativa L ., Coix lachryma jobi L ., Codonopsis javanica (Blume), Atractylodis macrocephala Koidz and Dioscorea persimilis Prain et Burkill against indomethacin-induced gastric ulceration and cysteamine-induced duodenal ulcer in rats. In the gastric lesion model, rats were divided into five groups, and were given distilled water or ranitidine (50mg/kg) or functional food (3.5 g/kg or 7g/kg) for seven days. On day 7, gastric ulceration was induced by a single intraperitoneal injection of indomethacin (30 mg/kg). In the model of duodenal ulcer, rats were also divided into 5 groups and were given distilled water, or ranitidine or functional food for seven days. On day 7, gastric ulceration was induced by a single intraperitoneal injection of cysteamine (400 mg/kg). The results show that the functional food powder had a gastroprotective effect by significantly reducing the gastric ulcer index and gastric ulcer lesions. In addition, the results also show that the functional food powder had a protective effect on the duodenum by significantly reducing the duodenal ulcer index and duodenal ulcer lesions. Keywords: Functional food, indomethacin, cysteamine, gastric ulcer, duodenal ulcer. References: [1] Chattopadhyay I, Bandyopadhyay U, Biswas K, Maity P, Banerjee RK. Indomethacin inactivates gastric peroxidase to induce reactive-oxygen-mediated gastric mucosal injury and curcumin protects it by preventing peroxidase inactivation and scavenging reactive oxygen. Free radical biology and medicine, 2006; 40: 1397-1408. [2] Minalyan A, Gabrielyan L, Scott D, Jacobs J, Pisegna JR. The Gastric and Intestinal Microbiome: Role of Proton Pump Inhibitors. Current Gastroenterology Reports, 2017; 19: 42. [3] Kim JW. NSAID-induced gastroenteropathy. The Korean journal of gastroenterology= Taehan Sohwagi Hakhoe chi, 2008; 52: 134-141. [4] Wallace JL, Keenan CM, Granger DN. Gastric ulceration induced by nonsteroidal anti-inflammatory drugs is a neutrophil-dependent process. American Journal of Physiology-Gastrointestinal and Liver Physiology, 1990; 259: G462-G467. [5] Allam MM, El-Gohary OA. Gastroprotective effect of ghrelin against indomethacin-induced gastric injury in rats: possible role of heme oxygenase-1 pathway. General physiology and biophysics, 2017; 36: 321. [6] Miller SL, Schlesinger G. Prebiotic syntheses of vitamin coenzymes: I. Cysteamine and 2-mercaptoethanesulfonic acid (coenzyme M). Journal of molecular evolution, 1993; 36: 302-307. [7] Dohil R, Gangoiti JA, Cabrera BL, Fidler M, Schneider JA, Barshop BA. Long-term treatment of cystinosis in children with twice-daily cysteamine. The Journal of pediatrics, 2010; 156: 823-827. [8] Selye H, Szabo S. Experimental model for production of perforating duodenal ulcers by cysteamine in the rat. Nature, 1973; 244: 458. [9] Warzecha Z, Ceranowicz D, Dembiński A, Ceranowicz P, Cieszkowski J, Kuwahara A, Kato I, Dembiński M, Konturek PC. Ghrelin accelerates the healing of cysteamine-induced duodenal ulcers in rats. Medical science monitor: international medical journal of experimental and clinical research, 2012; 18: BR181. [10] Inas Z, Hala AK, Gehan HH. Gastroprotective effect of Cordia myxa L. fruit extract against indomethacin-induced gastric ulceration in rats. Life Sci J, 2011; 8: 433-445. [11] Desai JK, Goyal RK, Parmar NS. Gastric and Duodenal Anti‐ulcer Activity of SKF 38393, a Dopamine D1‐Receptor Agonist in Rats. Journal of pharmacy and pharmacology, 1995; 47: 734-738. [12] Abdel‐Raheem IT. Gastroprotective Effect of Rutin against Indomethacin‐Induced Ulcers in Rats. Basic & clinical pharmacology & toxicology, 2010; 107: 742-750. [13] Szabo S, Haith LR, Reynolds ES. Pathogenesis of duodenal ulceration produced by cysteamine or propionitrile. Digestive diseases and sciences, 1979; 24: 471-477. [14] Jeitner TM, Lawrence DA. Mechanisms for the cytotoxicity of cysteamine. Toxicological sciences, 2001; 63: 57-64. [15] Khomenko T, Szabo S, Deng X, Ishikawa H, Anderson GJ, McLaren GD. Role of iron in the pathogenesis of cysteamine-induced duodenal ulceration in rats. American Journal of Physiology-Gastrointestinal and Liver Physiology, 2009; 296: G1277-G1286. [16] Min B, Gu L, McClung AM, Bergman CJ, Chen M-H. Free and bound total phenolic concentrations, antioxidant capacities, and profiles of proanthocyanidins and anthocyanins in whole grain rice (Oryza sativa L.) of different bran colours. Food Chemistry, 2012; 133: 715-722. [17] Wu T-T, Charles AL, Huang T-C. Determination of the contents of the main biochemical compounds of Adlay (Coxi lachrymal-jobi). Food chemistry, 2007; 104: 1509-1515. [18] He J-Y, Ma N, Zhu S, Komatsu K, Li Z-Y, Fu W-M. The genus Codonopsis (Campanulaceae): a review of phytochemistry, bioactivity and quality control. Journal of natural medicines, 2015; 69: 1-21. [19] Peng W, Han T, Xin W-B, Zhang X-G, Zhang Q-Y, Jia M, Qin L-P. Comparative research of chemical constituents and bioactivities between petroleum ether extracts of the aerial part and the rhizome of Atractylodes macrocephala. Medicinal chemistry research, 2011; 20: 146-151. [20] Saleha S, Saidi N, Rasnovi S, Iqbalsyah TM. Nutritional Composition of Dioscorea Hispida from Different Locations around Leuser Ecosystem Area. Jurnal Natural, 2018; 18: 1-6. [21] Sathish R, Vyawahare B, Natarajan K. Antiulcerogenic activity of Lantana camara leaves on gastric and duodenal ulcers in experimental rats. Journal of ethnopharmacology, 2011; 134: 195-197.